Justice in the Covid-19 era Through the Prism of Judicial Power - Victor Gorodovenko; Oleksandr Bondar; Larysa Udovyka (Ius Humani. Jornal do direito, 2021)
The work is devoted to identifying the main problems in the field of the principle of legal proceedings in the context of the Covid-19 pandemic. The research applies the formal-legal, historical and legal, comparative and modeling methodology. The order and issues to be considered are as follows: in the first section, we will consider the challenges and threats to justice that emerged during the Covid-19 pandemic. In the second section, we will see the judicial experience during the pandemic in the context of the basic principles of the judiciary. In the third section, we examine the application of organizational and procedural principles of the judiciary during the pandemic crisis. In the final fourth section, we will assess the role of international judicial institutions and government bodies in optimizing the administration of justice in the context of the Covid-19 pandemic. As a result of the work, emphasizing the vulnerability of the judicial system and justice standards, the authors support the expansion of exchange of experience and cooperation not only at the state level but also at the level of professional communities of judges, in particular with the members and judges of the European Commission for the Effectiveness of Justice, the Advisory Council of European Judges, and the European human rights courts.